2014
DOI: 10.1177/1535370214558022
|View full text |Cite
|
Sign up to set email alerts
|

Cynandione A attenuates lipopolysaccharide-induced production of inflammatory mediators via MAPK inhibition and NF-κB inactivation in RAW264.7 macrophages and protects mice against endotoxin shock

Abstract: Cynanchum wilfordii has been traditionally used in eastern Asia for the treatment of various diseases such as gastrointestinal diseases and arteriosclerosis. Cynandione A (CA), an acetophenone, is one of major constituents from roots of C. wilfordii. In the present study, the anti-inflammatory activities of CA were investigated in lipopolysaccharide (LPS)-treated RAW264.7 macrophages and LPS-administered C57BL/6 N mice. CA significantly decreased LPS-induced production of nitric oxide and prostaglandin E 2 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…1A), has been isolated in a number of studies (19,20). In addition, several studies investigating the biological and pharmaceutical activity of cA have revealed it exhibits protective activity against toxicity by various stimulant agents in rat hepatocytes and cortical neurons (21)(22)(23). Among investigations on the inhibitory effects of CA on anti-inflammatory activity, few have reported on the molecular mechanism underlying the anti-adhesion effects of CA in vascular inflammation.…”
Section: Cynandione a Inhibits Lipopolysaccharide-induced Cell Adhesimentioning
confidence: 99%
“…1A), has been isolated in a number of studies (19,20). In addition, several studies investigating the biological and pharmaceutical activity of cA have revealed it exhibits protective activity against toxicity by various stimulant agents in rat hepatocytes and cortical neurons (21)(22)(23). Among investigations on the inhibitory effects of CA on anti-inflammatory activity, few have reported on the molecular mechanism underlying the anti-adhesion effects of CA in vascular inflammation.…”
Section: Cynandione a Inhibits Lipopolysaccharide-induced Cell Adhesimentioning
confidence: 99%
“…Studies confirm lipopolysaccharide (LPS) induces inflammatory response in microglia/macrophage by activating several signaling pathways. Lipopolysaccharide first binds with membrane‐bound Toll‐like receptor 4 (TLR4), to activate its downstream signaling molecules, mainly mitogen‐activated protein kinases (MAPKs) and NF‐κB, through induction by phosphorylation . Phosphorylated MAPKs activate their downstream molecules, which can be translocated into the nucleus and contribute to expression of inflammatory molecules .…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide first binds with membrane-bound Toll-like receptor 4 (TLR4), to activate its downstream signaling molecules, mainly mitogen-activated protein kinases (MAPKs) and NF-κB, through induction by phosphorylation. [28][29][30] Phosphorylated MAPKs activate their downstream molecules, which can be translocated into the nucleus and contribute to expression of inflammatory molecules. 31 MAPKs consist of the JNK, p38 MAPK, and p42/p44 MAPKs.…”
Section: Discussionmentioning
confidence: 99%
“…The components of CWR are as follows: cynandione A [19], cynanoneside B, p-hydroxyacetophenone, 2,5-dihydroxyacetophenone, 2,4-dihydroxyacetophenone, wilfoside K1N, wilfoside C1N [20], β -sitosterol, wilfoside C3N, methyleugenol, wilfoside C1G, cynauriculoside A, daucosterol, acetovanillone, sucrose, geniposide, succinic acid, bungeiside A [21], and cynanchone A [22]. …”
Section: Phytochemistrymentioning
confidence: 99%
“…The components of CAR are the following: cynandione A [19]; cynanoneside B; p-hydroxyacetophenone; 2,5-dihydroxyacetophenone; 2,4-dihydroxyacetophenone; wilfoside K1N; wilfoside C1N [20]; C21-steroidal glycoside [23]; cyanoauriculosides F, G, and H [24]; wilfoside C3N [25]; taraxasterol acetate; cynanchone A; succinic acid; betulinic acid; kidjoranin [25]; auriculoside A [26]; caudatin; metaplexigenin; azelaic acid; wilforibiose; sucrose; 1-O-hexadecanolenin; beta-amyrin acetate; acetylquinol; beta-sitosterol; and daucosterol [27]. …”
Section: Phytochemistrymentioning
confidence: 99%